Effect of calcium supplementation in reducing adverse obstetric and perinatal outcomes: an umbrella review of systematic reviews and meta-analyses - Henok Kumsa; Mulugeta Wodaje Arage; Esuyawkal Mislu; Biruk Beletew Abate; Mihretab Mehari Reda; Moges Beriye; Atitegeb Abera; Nigus Bililign Yimer (Critical Public Health)
Background Calcium supplementation has been investigated as a potential intervention to prevent adverse obstetric and perinatal outcomes. However, the impact of calcium supplementation remains unclear due to conflicting results from various studies. Therefore, this study aims to provide a comprehensive umbrella review of the effect of calcium supplementation on adverse obstetrics and perinatal outcomes.Methods A systematic search was conducted in electronic databases (MEDLINE, Web of Science, SCOPUS, and Cochrane Library) from the first publication up to January 2024. A random-effects model meta-analysis was performed to estimate the effect of calcium supplementation on adverse obstetrics and perinatal outcomes.Results In this umbrella review, calcium supplementation reduced the risk of preeclampsia by 47% (RR: 0.53, 95% CI: 0.42, 0.68) with a considerable level of heterogeneity. Additionally, the risk of severe preeclampsia was reduced by 25% (RR: 0.75, 95% CI: 0.61, 0.92). Similarly, the risk of eclampsia was reduced by 30% (RR: 0.70, 95% CI: 0.54, 0.90). Moreover, calcium supplementation showed an effect on reducing the risk of low birth weight (RR: 0.88, 95% CI: 0.82, 0.94) and preterm birth (RR: 0.85, 95% CI: 0.77, 0.93) by 13% and 15%, respectively. However, it has no effect on reducing the risk of cesarean delivery, NICU admission, and stillbirth.Conclusion Calcium supplementation reduces the risk of preeclampsia, severe preeclampsia, eclampsia, and gestational hypertension. Additionally, it has little effect on reducing the risk of low birth weight and preterm birth. However, further research is needed to optimize the dosage, initiation, and duration of calcium supplementation.